Peran Teknologi Pertanian Cerdas (Smart Farming) untuk Generasi Pertanian Indonesia - Halawa, Destri Nugrahni (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Smart Farming or digital farming is a smart solution in the agricultural sector that utilizes an Internet of Things (IoT) based network system to carry out automatic monitoring and control in agricultural areas. The results of smart farming need to be defined and evaluated in order to increase farmers' understanding that smart farming can produce something new and positive. The benefits of smart agriculture will provide better changes to farmers' income and productivity, as well as improve the structure of socio-economic conditions, especially rural farmers. The current problem for farmers is that in order to make appropriate and correct decisions for the farming community in cultivating crops, real-time data regarding changes in the weather at that time is needed. So, through smart agricultural technology, this helps farmers find out real data. The effectiveness of agricultural technology is influenced by farmers' awareness and willingness to use and adopt agricultural innovations. Some of the technologies included in smart farming technology that can be used for agricultural productivity and efficiency, one of which is Agri drones which can be operated to spray pest and disease killers (pesticides), use liquid/solid fertilizers and better irrigation so as to avoid the use of fertilizers and pesticides. products that exceed the recommendations given. The presence of smart agricultural technology will make Indonesian agricultural cultivation more effective and efficient in determining how large or small the production and production needs are. Smart farming technology can help make the work of farmers easier in farming and for young people who want to become entrepreneurs in agriculture. Smart farming technology is similar to the use of technology needed to attract young people to participate in the agricultural sector, especially for the growth of Indonesian agriculture. This article is a review of previous research which will be followed up with research regarding the application of smart agricultural technology